Multi‐basin depositional framework for moisture‐balance reconstruction during the last 1300 years at Lake Bogoria, central Kenya Rift Valley. Issue 5 (17th February 2018) - De Cort, Gijs; Verschuren, Dirk; Ryken, Els; Wolff, Christian; Renaut, Robin W.; Creutz, Mike; Van der Meeren, Thijs; Haug, Gerald; Olago, Daniel O.; Mees, Florias
Abstract: Multi‐proxy analysis of sediment cores from five key locations in hypersaline, alkaline Lake Bogoria (central Kenya Rift Valley) has allowed reconstruction of its history of depositional and hydrological change during the past 1300 years. Analyses including organic matter and carbonate content, granulometry, mineralogical composition, charcoal counting and high‐resolution scanning of magnetic susceptibility and elemental geochemistry resulted in a detailed sedimentological and compositional characterization of lacustrine deposits in the three lake basins and on the two sills separating them. These palaeolimnological data were supplemented with information on present‐day sedimentation conditions based on seasonal sampling of settling particles and on measurement of physicochemical profiles through the water column. A new age model based on 210 Pb, 137 Cs and 14 C dating captures the sediment chronology of this hydrochemically complex and geothermally fed lake. An extensive set of chronological tie points between the equivalent high‐resolution proxy time series of the five sediment sequences allowed transfer of radiometric dates between the basins, enabling interbasin comparison of sedimentation dynamics through time. The resulting reconstruction demonstrates considerable moisture‐balance variability through time, reflecting regional hydroclimate dynamics over the past 1300 years. Between ca 690 and 950 AD, the central and southern basins of Lake Bogoria were reduced to shallow and separated brine pools. In the former, occasional near‐complete desiccation triggered massive trona precipitation. Between ca 950 and 1100 AD, slightly higher water levels allowed the build‐up of high pCO2 leading to precipitation of nahcolite still under strongly evaporative conditions. Lake Bogoria experienced a pronounced highstand between ca 1100 and 1350 AD, only to recede again afterwards. For a substantial part of the time between ca 1350 and 1800 AD, the northern basin was probably disconnected from the united central and southern basins. Throughout the last two centuries, lake level has been relatively high compared to the rest of the past millennium. Evidence for increased terrestrial sediment supply in recent decades, due to anthropogenic soil erosion in the wider Bogoria catchment, is a reason for concern about possible adverse impacts on the unique ecosystem of Lake Bogoria.